Living near violence: How proximity to violence shapes perceptions of police effectiveness and confidence in police. (November 2017) - Zahnow, Renee; Mazerolle, Lorraine; Wickes, Rebecca; Corcoran, Jonathan
Abstract: Living in close proximity to violent crime is associated with a number of negative outcomes including increased fear of crime and perceived risk of victimization. Living near violence may also undermine confidence in police. In this study we estimate fixed effects regression models to examine the association between spatial proximity to recent violence and perceptions of police while accounting for individual and neighborhood factors. Results indicate that living in close proximity to violence is associated with greater confidence in police and this relationship is mediated through perceived police effectiveness. We suggest people living closer to recent violent events are more likely to see police actively responding to crime and the coupling of seeing both the violence and police response results in people feeling more confident in police than those living further away from violence. Highlights: We examine the link between proximity to violence and perceptions of police. Living closer to a recent violent event predicted higher confidence in police. Perceived police effectiveness mediated the effect of proximity on confidence. Seeing police effectively respond to nearby violence may increase confidence.